Jurnal Jalan Jembatan - Jurnal Jalan Jembatan (Direktorat Bina Teknik Jalan dan Jembatan, 2026)
This section contains the cover, table of contents, foreword, and collection of abstracts for Volume 43, No. 1 (January–June 2026).